Social Networking Sites and Youth Transition: The Use of Facebook and Personal Well-Being of Social Work Young Graduates - Castillo de Mesa, Joaquin; Gómez-Jacinto, Luis; López Peláez, Antonio; Erro-Garcés, Amaya (Frontiers in Psychology, 2020)
Research on youth transitions, and the well-being of young people, has to take into consideration the digital context in which they are immersed. The digital interactions of young people increase year by year, online social networks play a key role in their personal and professional relationships, and a very high percentage of jobs require digital skills. According to Eurostat (2019), participating in social networking (one of the most common online activities in the EU-28), is growing every year (more than half (56%) of individuals aged 16 to 74 used the internet for social networking), and this percentage increases among the younger generations. In this article, we present the results of our research on the digital skills and well-being of young people on Facebook, with a sample of 126 young people graduated from the University of Malaga (School of Social Work) (Spain). Based on certain scales, the level of digital skills that students have on Facebook was measured, considering strategic aspects for information search, level of use and presence of Facebook in life, maintenance of relations and tolerance to diversity. Variables of psychosocial wellbeing were also measured (social capital, self-esteem, life satisfaction and personal wellbeing). Variables of digital skills on Facebook were subsequently related to wellbeing variables. Results show that certain digital skills relate to the wellbeing of young people. In this sense, we deem it crucial to develop education policies that could provide young graduates with general digital skills to be used in online networking sites.